Peningkatan aktivitas dan hasil belajar PPKN pada materi keberagaman sosial budaya masyarakat melalui penerapan model kooperatif tipe TGT kelas V Min 10 Aceh Besar - Rahmiati, Rahmiati (Universitas Serambi Mekkah, 2020)
The purpose of this study was to improve the activities and learning outcomes of PPKN on the material for Social and Cultural Diversity of the community of Grade V students of MIN 10 Aceh Besar. The learning model used in this study is the TGT type cooperative model. The subjects of this study were fifth grade students MIN 10 Aceh Besar. The number of students is 24 students with 11 male students and 13 female students. This research was conducted in the 2019/2020 school year within a period of 3 months, from September 2019 to November 2019 in the odd semester. The methodology of this research is Classroom Action Research (CAR) consists of two cycles and each cycle consists of two meetings. In each cycle consists of planning, implementation, observation and reflection. Data collection technique is to collect the value of the test carried out at the end of each learning in each cycle using the question instrument (written test). Observation data is done by looking at the activeness of students in the learning process. Data were analyzed by means of percentage statistics. The results showed that an increase in student learning activities in both cycles, from the category of being good enough and the good category increasing to very good. Completeness of student learning outcomes has increased from 45.83% in the pre cycle increased to 66.67% in the first cycle and increased to 83.33% in the second cycle. The use of the TGT type cooperative model can increase the activities and learning outcomes of PPKN on the material of Social and Cultural Diversity of Society V grade students MIN 10 Aceh Besar Academic Year 2019/2020.